2020
DOI: 10.1016/j.asmr.2019.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hip Translation In Vivo in Patients With Femoracetabular Impingement Syndrome Using 3-Dimensional Computed Tomography

Abstract: Purpose: To determine the 3-dimensional (3D) in vivo hip translation in patients with symptomatic femoroacetabular impingement syndrome (FAIS) using 3D computed tomography (CT) models with the hip in neutral and FABER (flexion, abduction, and the external rotation) positions and to identify patient predictors associated with the degree of hip translation. Methods: Seventy-eight patients with FAIS and cam lesions underwent CT scans in neutral and FABER positions. Demographics including age, sex, and body mass i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…These tools traditionally use a fixed center of rotation 28 . As demonstrated here and by Cvetanovich et al, 19 it is unlikely that femurs with cam morphology maintain a single point of rotation within the acetabulum. Further, studies have also shown that regions of minimum bone‐to‐bone distance do not necessarily correlate with the regions of femur‐labrum contact 28,29 .…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…These tools traditionally use a fixed center of rotation 28 . As demonstrated here and by Cvetanovich et al, 19 it is unlikely that femurs with cam morphology maintain a single point of rotation within the acetabulum. Further, studies have also shown that regions of minimum bone‐to‐bone distance do not necessarily correlate with the regions of femur‐labrum contact 28,29 .…”
Section: Discussionmentioning
confidence: 62%
“…One prior study using CT evaluated the translation of the femoral head between neutral and combined hip flexion, abduction, and external rotation (FABER) in individuals with FAI syndrome. 19 In their evaluation of two static positions, 29% of patients had total translations greater than 1 mm, with the average translation of all patients being 0.84 mm. While joint translations are not equivalent to bone-to-bone distances, we noted larger changes during dynamic activities.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Different types of femoroacetabular impingement can be confirmed by the evidence of abnormal mechanical contact/motion between the acetabular/labral side and the femoral head/neck during real-time imaging (with hip flexion and internal rotation; Video 6, http://links.lww.com/PHM/B711, Video 7, http://links.lww.com/PHM/B712, Video 8, http://links.lww.com/PHM/B713). 9,10 To assess femoral head instability, the hip joint is stressed using the “apprehension position.” To achieve stress on the anterior structures, the patient holds the contralateral knee to maintain the contralateral hip flexion in the supine position. Meanwhile, the ipsilateral hip is being extended, the knee is flexed, and the shin hangs over the bed.…”
Section: Anterior and Medial Viewmentioning
confidence: 99%
“…It has been previously established that the hip does not simply rotate in its socket but also exhibits translational movements as well [1,2,6,13,16,22]. Recently, biomechanical models have shown that capsular laxity increases femoral head rotation and translation [8][9][10].…”
mentioning
confidence: 99%